Math, asked by sathvikchandra1875, 3 months ago

If the zeros of x
2 + ax + b are two consecutive integers, then prove that a
2 = 1 + 4b.

Answers

Answered by mathdude500
1

\large\underline{\sf{Given- }}

The zeroes of the polynomial x² + ax + b are two consecutive integers.

\large\underline{\sf{To\:prove - }}

\rm :\longmapsto\: {a}^{2}  = 1 + 4b

\large\underline{\sf{Solution-}}

Given that

The zeroes of the polynomial x² + ax + b are two consecutive integers.

Let assume that zeroes of the polynomial be y and y + 1.

We know that,

In a quadratic polynomial,

\boxed{\red{\sf Sum\ of\ the\ zeroes=\frac{-coefficient\ of\ x}{coefficient\ of\ x^{2}}}}

So,

Using this result we have

\rm :\longmapsto\:y + y + 1  =  -  \: \dfrac{a}{1}

\rm :\longmapsto\:2y + 1 = a

\rm :\longmapsto\:y = \dfrac{a - 1}{2}  -  -  - (1)

Also, we know that,

In quadratic polynomial,

\boxed{\red{\sf Product\ of\ the\ zeroes=\frac{Constant}{coefficient\ of\ x^{2}}}}

\rm :\longmapsto\:y( y + 1)  = \: \dfrac{b}{1}

On substituting the value of y from equation (1), we get

\rm :\longmapsto\:\bigg(\dfrac{a - 1}{2}  \bigg)\bigg(\dfrac{a - 1}{2}  + 1 \bigg)  = b

\rm :\longmapsto\:\bigg(\dfrac{a - 1}{2}  \bigg)\bigg(\dfrac{a - 1 + 2}{2} \bigg)  = b

\rm :\longmapsto\:\bigg(\dfrac{a - 1}{2}  \bigg)\bigg(\dfrac{a + 1}{2} \bigg)  = b

\rm :\longmapsto\: {a}^{2} - 1 = 4b

\rm :\longmapsto\: {a}^{2} = 4b + 1

Hence, Proved.

Additional Information :-

\rm :\longmapsto\: \alpha , \beta , \gamma  \: are \: zeroes \: of \: a {x}^{3}  + b {x}^{2}  + cx + d, \: then

 \red{\boxed{ \bf{ \:  \alpha +   \beta  +  \gamma  =  -  \: \dfrac{b}{a} }}}

 \red{\boxed{ \bf{ \:  \alpha \beta  +   \beta \gamma   +  \gamma \alpha   = \: \dfrac{c}{a} }}}

 \red{\boxed{ \bf{ \:  \alpha  \beta  \gamma  =  -  \: \dfrac{d}{a} }}}

Similar questions